IDENTIFICATION OF PHYSICAL MISCONCEPTIONS AND THEIR CAUSES USING FIVE-TIER KINEMATICS TEST (FTKT) ON HIGH SCHOOL STUDENTS - Nurul Naasyithotul Jannah; Winny Liliawati; Muslim Muslim; Novia Aditya (Journal of Teaching and Learning Physics, 2022)
This study aims to identify misconceptions in physics concepts and find out the causes of misconceptions. This type of research is descriptive quantitative research. The research instrument used a five-tier diagnostic test. Determination of samples taken by purposive sampling technique. This research was conducted on 120 students with 55 male and 65 female students from senior high schools in West Bandung Regency and three high schools in Majalengka Regency. Based on the validation results, it shows that the 12 items are categorized as valid and the reliability value is 0.93 which is included in the very good category. The misconceptions identified with the largest percentage are in the concepts of distance, position, and displacement of 49.17%.